Differences in Determining Ramadan and Shawwal: A Discourse Analysis of the Book Nusus al-Akhyar fi al-Shaum Wa al-Ifthar - Ningsih, Ika Wahyu; Febriyanti, Fitri; Rizki, Iqbal Ainur (Universitas Islam Sultan Agung, 2023)
The phenomenon of differences in the implementation determination of Eid al-Fitr in 1418 H was regretted by the Indonesian people. Responding to the emergence of differences in the determination of 1418 H, KH Maimoen Zubair through his work Nusuus al-Akhyar fi Al-Shum wa Al-Iftihar intends to provide solutions to Muslims in Indonesia in facing the differences surrounding the determination of Eid al-Fitr. This type of research is qualitative research with the research approach used being discourse analysis initiated by Van Dijk. The data used in this study consisted of primary data and secondary data. Primary data are in the form of lexemes, words, phrases, and sentences in Arabic that contain ideas about the determination of the beginning of the month of Ramadan and Shawwal in the book. Secondary data come from sources, journals, print media, online journalism, and other scientific works to find out the context of social situations that can influence the writing of the book. Data collection methods in this study are interviews and literature study. The results showed that the linguistic aspect that stands out in the discourse of persuasion is the invitation to promote unity in the midst of controversy over differences in each group; the author's ideology appears in the title, the lexemes